Tidal and residual currents observations at the San Matías and San José Gulfs, Northern Patagonia, Argentina - Moreira, Diego (2009)
Four current time series, collected at costal locations of the San Matías and San Jose' gulfs, Argentina, are analyzed for tidal and residual currents. Tides dominate San Matías Gulf dynamics, accounting for more than 72% of the variance, whereas winds dominate at San José Gulf, explaining approximately 70% of the variance. Tides display a dominating semidiurnal regime, in compliance with what is know from the few tidal stations available and numerical simulations. At San Matías, coastal tidal currents speed increases northward, exceeding 0.6 m 8-1 at San Antonio Este. Higher order harmonics because of nonlinear interactions are large; in every sampled site, M4 and M6 currents are stronger than the diurnal constituents and have amplitudes around 5% of those from M2. At Las Grutas (San Matías Gulf), simultaneous wind observations were collected. Currents respond almost instantaneously to wind variability in the form of two modes. The first one results from winds blowing along the northwest-southeast axis and is very weak; the second one results from winds blowing from any other direction and is characterized by strong meridional currents. Even though bimodal patterns are typical of semienclosed basins, the characteristic wind directions in this gulf are not related with the orientation of its mouth but could result of the circulation in the form of two gyres suggested by numerical simulations. Energy peaks are observed at the 4 to 8 days' band and at around 12 and 20 days. Therefore, currents rapidly respond to wind variability in every timescale, from synoptic to intraseasonal.